PEMBERANTASAN BUTA AKSARA AL-QURAN DI RUMAH KALIGRAFI AN-NIDA’ MEDAN-SUMATERA UTARA - Ulfa Aini; Nurul Jumadissaniyah Sitorus; Al Halim Kusuma (Jurnal Ekshis, 2025)
The challenge of Qur'an illiteracy is a serious obstacle in communities and institutions, limiting access to the interrelated understanding of the Qur'an and Arabic language learning. The development of science and technology is a challenge for Arabic language educators in improving the quality of learning. The art of calligraphy or khatt has emerged as an effective potential in overcoming illiteracy in the Koran and enriching Arabic language learning. Calligraphy is described as a beauty of taste, an advisor to the mind, a weapon of knowledge, and a secret keeper. This research discusses teachers' efforts to improve the ability to read and write the Qur'an through the art of calligraphy. Calligraphy is not only an aesthetic aspect, it is also a maharah kitabah, the ability to compose hijaiyah letters according to the rules of good and correct Arabic writing. The research methods used include literature review, direct interviews, observation and documentation. The research results show that through calligraphy training, efforts to help overcome Hijaiyah illiteracy are carried out by detecting individual abilities, designing learning programs, and assessing learning outcomes. Calligraphy is an effective instrument for overcoming illiteracy and increasing Arabic literacy. The success of learning calligraphy depends on an approach that suits individual needs. The art of calligraphy is not only a learning tool, but also brings the spiritual values ​​and beauty of the Koran to generations learning Arabic.